Unveiling the Hidden Risks of Capital Inflows on Non-Financial Firm Performance in Indonesia - Hesti Werdaningtyas; Noer Azam Achsani; Anny Ratnawati; Tony Irawan (International Institute for Advanced Science & Technology (IIAST), 2026)
The limited research on the impact of external debt on financial system stability at the micro level creates a clear need for further investigation. The positive contributions to the relevant discourse of this study lie in its attempt to address that gap by conducting a comprehensive micro panel data analysis, covering the performance of 523 individual Non-Financial Corporations (NFCs) in Indonesia, based on panel data. Additionally, this study employs advanced methodology, utilising a dynamic model and System-Generalised Methods of Moments (Sys-GMM) estimation. The research have tackled endogeneity issues using GMM estimators to ensure the robustness of our findings. The results indicate that different capital flows exert varying impacts on corporate performance. In particular, private external debt inflows and Portfolio Investments (PI) have a positive influence on the financial stability of firms. Conversely, direct investment in manufacturing firms and corporate credit growth have a significant impact on corporate financial stability. From a macroprudential policy perspective, the findings highlight the importance of monitoring corporate vulnerabilities, as it may pose risks to the banking sector. These insights provide valuable guidance for policymakers in developing more effective external debt management strategies to ensure financial stability.